PEMBELAJARAN AL-QUR’AN PADA KEGIATAN TASQIF DI YAYASAN IMTIYAZ INSAN MULIA KOTA PROBOLINGGO - Wildani Firdaus; Faridi Faridi; Moh.Nurhakim Nurhakim (JURNAL TARBIYAH, 2024)
This study examines the learning of the Qur'an in TASQIF activities at the Imtiyaz Insan Mulia Foundation in Probolinggo City, which aims to describe and analyze the implementation of learning the Qur'an and the application of the Jibril method in TASQIF activities at the Imtiyaz Insan Mulia Foundation in Probolinggo City. This research method applies a qualitative approach with a case study research type. To collect the required data, the author uses several techniques, namely observation, interviews, and documentation related to learning the Qur'an. Data analysis was conducted using an exploratory descriptive approach, including data reduction, display, and verification. The results of this study state that (1) The implementation of Al-Qur'an learning in TASQIF activities at the Imtiyaz Insan Mulia Foundation in Probolinggo City only focuses on learning to read the Al-Qur'an (tahsin) according to its makhraj and tajwid without adding other content. The learning concept places more emphasis on individual teaching (ta'lim munfaridi), (2) In TASQIF activities, teachers apply the Jibril method with the talqin-taqlid (imitation) technique. This method is centered on the teacher (teacher center).